Predisposing factors for dental trauma, República de Angola elementary school, 2012-2013 - Patricia Grisel Sanchez Barrio; Leonardo Sanchez Santos; Julia Perez Piñeiro; Elizabeth de la Torre Rodriguez (Editorial Ciencias Médicas, 2015)
Introduction: traumatic dental injuries are a current health problem. The scientific literature on the subject refers to a number of predisposing factors for dental trauma which may be acted upon preventively. Objective: identify the frequency of predisposing factors for dental trauma among the school age children studied. Methods: a descriptive cross-sectional study was conducted with boys and girls aged 7-12 from República de Angola elementary school in the municipality of Boyeros from 2012 to 2013. The variables studied were age, sex, presence of traumatic injury, type of deforming oral habit, profile, labial competence, overbite, overjet. The summary measurements used were absolute frequencies and percentages. Results: the 11-12 age group was the best represented with 65 children (67 %). There was a predominance of the male sex (68 %) among children with traumatic injuries. The most common deforming oral habit was thumb sucking (57.7 %). Of the children with antecedents of traumatic injuries, 97 had a convex profile (73.2 %). Increased overjet was found in 88.7 % of the children with dental trauma. Bilabial incompetence was found in 83.5 % of the children with antecedents of traumatic injuries. Of the children with dental trauma, 48.5 % had a negative overjet. Conclusions: the most common predisposing factors were increased overjet, convex profile, bilabial incompetence, negative overjet and deforming oral habits, among which thumb sucking was predominant.